Biostatistical analysis - Zar, Jerrold H. (Prentice Hall, 1999)
The latest edition of this best-selling biostatistics book is both comprehensive and easy to read. It provides a broad and practical overview of the statistical analysis methods used by researchers to collect, summarize, analyze, and draw conclusions from biological research data. The Fourth Edition can serve as either an introduction to the discipline for beginning students or a comprehensive procedural reference for today's practitioners.